Early diagnosis of Hantavirus infection by family doctors can reduce inappropriate antibiotic use and hospitalization - Brorstad, Alette; Oscarsson, Kristina Bergstedt; Ahlm, Clas (Scandinavian journal of primary health care, 2010)
Abstract Objective. Hantavirus infections are emerging infections that cause either Hantavirus pulmonary syndrome or haemorrhagic fever with renal syndrome (HFRS). A recent Swedish outbreak of nephropathia epidemica, a European HFRS, was analysed to study the patient flow and clinical picture and to investigate the value of an early diagnosis in general practice. Design. In a retrospective design, medical records of verified cases of Hantavirus infection were studied. Setting. The study was conducted in the county of Norrbotten, Sweden. Subjects. Data from Hantavirus patients diagnosed between 2006 and 2008 were analysed. Main outcome measures. Demographic data, level of care, treatment, clinical symptoms, and laboratory findings were obtained. Results. In total, 456 cases were included (58% males and 42% females). The majority of patients first saw their general practitioner and were exclusively treated in general practice (83% and 56%, respectively). When diagnosed correctly at the first visit, antibiotics and hospitalization were significantly lowered compared with delayed diagnosis (14% vs. 53% and 30% vs. 54%, respectively; p < 0.0001). The clinical picture was diverse. Early thrombocytopenia was found in 65% of the patients, and haemorrhagic manifestations were documented in a few cases. Signs of renal involvement - haematuria, proteinuria, and raised levels of serum creatinine - were found in a majority of patients. Conclusions. Raised awareness in general practice regarding emerging infections and better diagnostic tools are desirable. This study of a Hantavirus outbreak shows that general practitioners are frontline doctors during outbreaks and through early and correct diagnosis they can reduce antibiotic treatment and hospitalization.